Stamp-Seals and Sealings from Tell Dothan - Miglio, Adam E. (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
Tell Dothan lies in the Dothan Valley of northern Palestine. This valley connects the Jezreel with the Plain of Sharon, approximately 10 kilometers from the hill country where modern-day Jenin sits. The site was excavated by Joseph P. Free on behalf of Wheaton College for 10 seasons over the course of 12 years, from 1953-1964 (Figure 1).